The Subject Identity in The Growing Space of a Tourism Village: A Case study of Sidomulyo Village Flower Market - Hayat, Muhammad; Ishomuddin, Ishomuddin; Darvina Soedarwo, Vina Salviana; Sukmana, Oman (Technium Social Sciences Journal, 2025)
The transformation of rural spaces into tourism destinations often reshapes the identity of local communities and their interaction with physical and social landscapes. This study examines the evolving subject identity within the growing spatial context of Sidomulyo Village, known for its flourishing flower market. Employing a qualitative case study approach, this research explores how tourism development has influenced the socio-cultural, economic, and spatial dimensions of the village. Data were gathered through in-depth interviews, field observations, and document analysis to identify key factors shaping identity construction. Findings reveal that the village’s transition to a tourism hub fosters both opportunities and challenges, with local identity being negotiated between traditional agricultural roots and emerging market demands. The study contributes to broader discourses on rural tourism development, spatial dynamics, and community identity, offering insights into sustainable practices for balancing growth with cultural preservation.